Feminism in contemporary Gongbi painting: formal analysis perspective - Runhong, Liu; Ahmed Fauzi, Tetriana; Mohd Rozlan, Rosyida (Universiti Teknologi MARA, Perak, 2025)
This study focuses on the aesthetic characteristics of female artists and the representation of female figures in contemporary Gongbi painting. Traditionally known for its meticulous brushwork and detailed expression, Gongbi painting has undergone a transformation, adapting to modern contexts by integrating contemporary aesthetics, cultural narratives, and individual expression. In recent decades, female artists have played a crucial role in reshaping the genre, infusing it with new meanings and perspectives rooted in gender awareness and personal experience. The existing literature discusses the impact of feminism and the increasing presence of women in the art world, shedding light on how these factors influence both content and style. Scholars such as Kim, Elgammal, and Mazzone argue that formal elements—such as line quality, texture, and color—can be critically analyzed to understand an artwork's aesthetic values. Building on this approach, the present study applies formal analysis to examine the works of nine Chinese female artists, highlighting their contributions to the evolution of contemporary Gongbi painting.